Competition or cooperation? Research on the spatial game relationship of regional carbon emission efficiency - Chen, Weiguo; Chen, Xiangtang; Weng, Erxuan; Dong, Yufeng; Sun, Yi; Zou, Liping (Frontiers in Energy Research, 2024)
The gradient differences of economic development and industrial structure differences in Jing-Jin-Ji Region are significant. The ability of Jing-Jin-Ji Region to pay for environmental protection is imbalanced. The above two situations make it difficult to achieve coordinated pollution reduction and carbon reduction governance. Accurately measuring carbon emission efficiency and thoroughly analyzing the cooperation and competition relationship of regional carbon emission reduction based on fully considering stakeholders are of great significance for the joint construction, prevention and control of regional ecological environment. The research is also of great significance for promoting high-quality economic development and ensuring effective protection of the regional ecological environment. This study combines game theory and DEA theory to measure the carbon emission efficiency of the Jing-Jin-Ji Region, and then uses spatial game theory to analyze the average degree of being attacked, anti-attack ability, strongest attacker, and optimal partner for the carbon emission efficiency of different DMUs. The study concluded that: 1) Xicheng District and Hedong District have higher carbon emission efficiency, while Mentougou District, Fengtai District, Changping District, Fangshan District, Shijingshan District, Pinggu District and Yanqing County have the lowest carbon emission efficiency. 2) From an analysis of the degree of being attacked, it can be observed that economically developed areas experience a higher average degree of being attacked compared to economically underdeveloped areas. In regions with lower economic development, the influence of the local government on reducing carbon emissions is not significant, whether acting independently or in collaboration. Regions with contrasting industrial structures could be ideal partners, and areas with higher carbon emission efficiency could collaborate with regions with lower carbon emission efficiency to achieve greater reduction potential.